Urogryllus toledopizai: A NEW SPECIES OF CRICKET FROM SOUTHEASTERN BRAZIL (ORTHOPTERA: GRYLLIDAE: GRYLLINAE) - Mello, Francisco de A. G. de (REVISTA DE AGRICULTURA, 2015)
Urogryllus toledopizai: A NEW SPECIES OF CRICKET FROM SOUTHEASTERN BRAZIL (ORTHOPTERA: GRYLLIDAE: GRYLLINAE)